Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires